2005
DOI: 10.1111/j.1600-6143.2005.01035.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and Risk Factors for Recurrent Scleroderma Renal Crisis in the Kidney Allograft: Case Report and Review of the Literature

Abstract: Scleroderma renal crisis (SRC) can lead to end-stage renal disease (ESRD) and subsequent need for dialysisand/or renal transplantation. We review all reported cases of renal transplantations in scleroderma patients from PubMed search, present UNOS data on transplant outcomes, and identify predictors for allograft SRC. Of the five cases with recurrent SRC, all developed ESRD within a year of onset of native kidney SRC, whereas none of those who developed ESRD more than 1-2 years after the onset of SRC developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
1
9

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 16 publications
(27 reference statements)
1
49
1
9
Order By: Relevance
“…Ansonsten ist die Nierentransplantation eine wichtige Behandlungsoption. Die 5-Jahres-Überlebensrate der Transplantate beträgt 56,7%, mit einem Rezidiv der Erkrankung nach Transplantation in 6,7% [40]. Calcineurininhibitoren können eine ARC begünstigen und werden daher bei transplantierten Patienten mit SyS nicht empfohlen.…”
Section: » Calcineurininhibitoren Können Eine Arc Begünstigenunclassified
“…Ansonsten ist die Nierentransplantation eine wichtige Behandlungsoption. Die 5-Jahres-Überlebensrate der Transplantate beträgt 56,7%, mit einem Rezidiv der Erkrankung nach Transplantation in 6,7% [40]. Calcineurininhibitoren können eine ARC begünstigen und werden daher bei transplantierten Patienten mit SyS nicht empfohlen.…”
Section: » Calcineurininhibitoren Können Eine Arc Begünstigenunclassified
“…Am Anfang des Geschehens steht vermutlich eine autoantikörperindu-zierte Endothelschädigung. Rekurrenzen im Transplantat finden sich bei 3,5-45% und treten bereits in den ersten 1-2 Jahren nach Transplantation auf [26]. Risikofaktor für eine Rekurrenz ist eine rasche, progrediente Insuffizienz der Eigennieren (innerhalb von einem Jahr).…”
Section: Systemische Skleroseunclassified
“…Post-transplant recurrence of SRC has been reported even after transplantation from a twin sister (Caplin, Dikman, Winston, Spiera, & Uribarri, 1999;Woodhall, McCoy, Gunnells, & Seigler, 1976). Pham et al (Pham, et al, 2005) suggested that SRC recurrence occurs early in the post-transplantation course. However, Cheung et al (Cheung, et al, 2005) challenged this view when describing a late SRC recurrence observed seven years post-transplantation.…”
Section: Transplantationmentioning
confidence: 99%
“…In SRC, graft and patient survival post-transplantation is inferior to general renal transplant patient (Pham et al, 2005). Recurrence of scleroderma may participate in this poor outcome (Cheung, Gibson, Rush, Jeffery, & Karpinski, 2005).…”
Section: Transplantationmentioning
confidence: 99%